The Impact of IK-CEPA (Indonesia-South Korea Comprehensive Economic Partnership Agreement) for Indonesia - Nabila Salsa Bila; Hasna Wijayati (Formosa Journal of Sustainable Research, 2022)
The Indonesia-Korea Comprehensive Economic Partnership Agreement (IK-CEPA) was an economic cooperation that includes a comprehensive free trade agreement that discusses issues of trade, investment, services, and Intellectual Property Rights (IPR) and has mutual relations. So as to form an access chain pattern in the form of market access, access to capacity development, and facilitation of trade and investment carried out by Indonesia and South Korea. The discussion in this study focuses on the impact that Indonesia gets from the IK-CEPA, escpecially in 2020 because 2020 was an important milestone in the establishment of economic relations between Indonesia and South Korea. South Korea was interested in making Indonesia a new production base in ASEAN and as a production hub to enter regional and world markets. The method used was a descriptive research method with qualitative approach analysis. The aim was to use a descriptive method to determine the impact that Indonesia gets from the IK-CEPA. Thus, it was obtained that the Indonesia-Korea Comprehensive Economic Partnership Agreement (IK-CEPA) provides considerable benefits for Indonesia, such as the entry of investment from South Korea, skills training and student exchange, and the provision of trade facilitation for Indonesia